1994
DOI: 10.1007/bf01839285
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-reactive protein and immune responses in dogs inoculated withBordetella bronchiseptica (phase I cells)

Abstract: Eight Beagle dogs were inoculated intrabronchially with 5 x 10(9) live, avirulent cells of Bordetella bronchiseptica L-414 strain (phase I cells) (B. bronchiseptica) to investigate the serum levels of their C-reactive protein, the white blood cell counts, the antibody responses to B. bronchiseptica in the sera and tracheal secretions, and the effects of prednisolone given to four of the dogs on C-reactive protein (CRP), white blood cells (WBC) and immune responses. In two Beagle dogs inoculated intrabronchiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 20 publications
(16 reference statements)
2
44
1
3
Order By: Relevance
“…Other acute phase proteins include haptoglobin, and serum amyloid A (SAA). Increased levels of a number of these acute phase proteins have been associated with respiratory diseases of domestic animals [39,66,68,113,143,144]. An excellent review of the application of the acute phase proteins in veterinary clinical chemistry is available [99].…”
Section: Serum Proteinsmentioning
confidence: 99%
“…Other acute phase proteins include haptoglobin, and serum amyloid A (SAA). Increased levels of a number of these acute phase proteins have been associated with respiratory diseases of domestic animals [39,66,68,113,143,144]. An excellent review of the application of the acute phase proteins in veterinary clinical chemistry is available [99].…”
Section: Serum Proteinsmentioning
confidence: 99%
“…In addition, Kono et al (19) found that in B. bronchiseptica infections of pigs there was no correlation between the clearly developing antibody response and protection from colonization or disease. However, the same study also showed that 21 days may be insufficient for the development of serum antibodies to B. bronchiseptica in pigs, whereas in dogs serum IgG production occurs 5 days postinfection (33).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, a study with piglets (24) has shown that antibodies to B. bronchiseptica LPS have a limited role in protection, even though they are produced following vaccination. However, IgA titers correlated with the development of resistance to clinical infection (7) and several authors (11,27,33) found that local antibodies were protective against B. bronchiseptica. In fact, both Shade and Goodnow (27) and Ellis et al (11) reported protection against B. bronchiseptica following intranasal vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum concentration of CRP was not affected in the experimentally inoculated group treated with prednisolone [24]. SAA values were signifi cantly increased one day after Bordetella bronchiseptica inoculation in dogs [25].…”
Section: Dogsmentioning
confidence: 84%